Anthropo-Physiometric Features and Analysis of the Body Composition of Yakut Youth of Early and Late Puberty in the Republic of Sakha (Yakutia) - Lena I. Arzhakova (International Journal of Biomedicine, 2019)
The aim of this study was to assess the anthropometric and physiometric indicators with an analysis of the body composition of young Yakuts of early and late puberty, living in the Republic of Sakha (Yakutia) (RS(Y)). Materials and Methods: A total of 184 indigenous youths aged from 14 to 17 years, permanently residing in RS(Y), were examined. The study used generally accepted methods: anthropometry, dynamometry, spirometry, caliperometry, and body composition assessment by bioelectrical impedance analysis. Results: Among Yakut youth living in RS(Y), an increase in musculoskeletal mass and a decrease in fat mass was observed in groups aged 14 to 17. In the period from 14 to 17 years, Yakut youth show significantly increased indicators of dynamometry, deadlift and vital lung capacity. The data above are accompanied by a decrease in the indicators of the content of fat mass and an increase in lean body mass, musculoskeletal mass and body cell mass. There is growth not only in skeletal muscles and skeleton, but also in the mass of internal organs. The data obtained will be used to develop an interval classification of body composition parameters for males of different ages in order to develop standards of physical development specifically for people living in RS(Y).